THE IMPACT OF USING YOUTUBE SOCIAL MEDIA ON STUDENTS' POSITIVE BEHAVIOR IN INDONESIAN LANGUAGE CLASS V AT SD INPRES BONTOMANAI - Ashar Ashar; Meisar Ashari; Fitri Maharani Hamsah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This type of research is quantitative research with a one-group pre-test-post-test design. The sample and population are fifth-grade students at SD Inpres Bontomanai, totaling 25 students. The instruments used to collect data were pretest, posttest, and positive behavior questionnaires of students. The data analysis technique used is descriptive analysis technique and inferential analysis technique. The results of this study are the average post-test results of 79.44. based on the results of hypothesis testing using the one-sample t-test, a significance value of p(sig.(2.Tailed) is 0.000 because p <0.05 then H0 is rejected and H1 is accepted. It can be said that there is an influence of social media youtube on students' positive behavior in the subject of Indonesian language class V SD Inpres Bontomanai